2017
DOI: 10.1016/j.ejvs.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Initial Misdiagnosis of Ruptured Abdominal Aortic Aneurysms on Lead Times, Complication Rate, and Survival

Abstract: Misdiagnosis is common in patients with rAAA, and treatment is significantly delayed in misdiagnosed patients. The study did not show any survival disadvantage or increased frequency of post-operative complications in misdiagnosed patients despite the delayed treatment. However, only patients who reached surgical intervention were included in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…There have been some studies analyzing the impact of initially misdiagnosed true aneurysms [17,18], but none so farto our knowledgeanalyzed the frequency and reasons for missed or delayed diagnosis of VAPA. We found that more than half (58 %) of our patients had been initially misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies analyzing the impact of initially misdiagnosed true aneurysms [17,18], but none so farto our knowledgeanalyzed the frequency and reasons for missed or delayed diagnosis of VAPA. We found that more than half (58 %) of our patients had been initially misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Tipični simptomi i znaci za RAAA su naglonastali bol u leđima ili trbuhu, hipotenzija i palpabilno pulsirajuća masa u epi i/ili mezogastrijumu [13,14]. Kod izrazito gojaznih [15] ili hipotenzivnih bolesnika, palpiranje pulsirajuće mase može biti otežano ili neizvodljivo.…”
Section: Kako šTo Ranije Postaviti Pravu Dijagnozu?unclassified
“…Presudan faktor za poboljšanje rezultata lečenja RAAA je vreme, iz čega proizilazi da bi u inicijalnom tretmanu ovakvih bolesnika trebalo da postoji jasno definisana vremenska linija što zahteva uvođenje posebnih protokola za ovakve slučajeve [34][35][36]. Prema Vodiču udruženja za vaskularnu hirurgiju, preporučeno ciljno vreme od prvog kontakta sa bolesnikom do uspostavljanja hemostaze iznosi 90 minuta [40].…”
Section: Osnovni Principi Reanimacije I Tretmana Tokom Prvog Kontaktaunclassified
“…Comprehensive clinical data from the registry can be combined with data from governmental registries and thereby provide an important source for research and quality improvement [6][7][8][9][10][11]. Another advantage is the feasibility of collecting data on rare diseases, which for example, has been done for ruptured popliteal artery aneurysms, mycotic aneurysms and vascular injuries [12][13][14][15][16].…”
Section: Schlüsselwörtermentioning
confidence: 99%